The Belhar Confession – 29 years on - Nico, Horn (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Twenty-nine years down the line, this essay revisits the birth of the Belhar confession in 1982. It describes the immediate reaction in South Africa, specifically by the Dutch Reformed Church, to the acceptance of this confession by the then Dutch Reformed Mission Church. It shows how the confession was “held hostage” by church politics in the Dutch Reformed family of churches in South Africa from 1982 until 1994, constituting and continuing to constitute, a major stumbling block for efforts of reunification between the DRC and DRMC (and later, URCSA) – either to the chagrin or relief of those involved. In light of the continued importance of this confession with regard to the issue of church reunification and its positive reception over time in some North American and European Reformed churches, the article calls for a reconsideration of the possible role the confession can play in a new millennium, in a vastly different South African church and society and in a time thinking about confessions seem to be closer to those of Calvin and the Reformers, and of Karl barth, steering away from the dogmatic Dordt way in which it for long understood by many Dutch Reformed Christians in South Africa.